PWE-012 Colonoscopic adverse events in St Mark's bowel cancer screening experience. (23rd September 2015) - Gupta, S; Vance, M E; Suzuki, N; Fraser, C; Saunders, B P; Thomas-Gibson, S
Abstract : Introduction: The incidence of polyps requiring therapy is higher in Bowel Cancer Screening (BCS) compared to the symptomatic population. The current BCS patient information leaflets quote "heavy" bleeding risk of 1:150 and perforation 1:1500. Methods: To assess all complications 2006–2009. Data were collected prospectively. Additional information was retrieved from the screening team. Result: 1253 procedures were performed in this period. 583 patients had 1625 polyps requiring polypectomy. There were eight (0.6%) reported adverse events and five (0.4%), recalled by screening team (Abstract 012 ). Conclusion: Less than 1:500 patients undergoing polypectomy required transfusion. Overall bleeding risk (including small bleeds without transfusion) was ∼1:80 patients requiring polypectomy. Admission risk was 0.6%. Perforation risk was ∼1:1200 colonoscopies and ∼1:600 patients requiring polypectomy. No patients required surgery or prolonged admission, with no procedure related mortality. Despite a higher therapeutic load in the BCS cohort, the risk of significant complications was within acceptable ranges.